Biodegradation and hydrolysis of rice straw with corn steep liquor and urea-alkali pretreatment - Ma, Yulin; Chen, Xu; Zahoor Khan, Muhammad; Xiao, Jianxin; Liu, Shuai; Wang, Jingjun; Alugongo, Gibson Maswayi; Cao, Zhijun (Frontiers in Nutrition, 2022)
The current study evaluated the corn steep liquor (CSL) and urea-alkali pretreatment effect to enhance biodegradation and hydrolysis of rice straw (RS) by ruminal microbiome. The first used RS 1) without (Con) or with additives of 2) 4% CaO (Ca), 3) 2.5% urea plus 4% CaO (UCa) and 4) 9% corn steep liquor + 2.5% urea + 4% CaO (CUCa), and then the efficacy of CSL and urea-alkali pretreatment was evaluated both in vitro and in vivo. The Scanning electron microscopy, X-ray diffraction analysis, cellulose degree of polymerization and Fourier-transform infrared spectroscopy, respectively results showed that CSL and urea-alkali pretreatment altered the physical and chemical structure of RS. CSL and Urea-alkali pretreated enhanced microbial colonization by improving the enzymolysis efficiency of RS, and specially induced adhesion of Carnobacterium and Staphylococcus. The CUCa pretreatment could be developed improve RS nutritional value as forage for ruminants, or as feedstock for biofuel production.